When catalysis meets spintronic: the emergence of spintro-catalysis and the potential of mixed-anion spinels - Aschauer, Ulrich; Kabbour, Houria (Dalton transactions : an international journal of inorganic chemistry, 2025)
The emerging field of spintro-catalysis, at the interface of catalysis and spintronics, offers a compelling strategy to overcome long-standing limitations in catalytic reactions involving spin-sensitive intermediates. In particular, the redox chemistry of molecular oxygen, central to the oxygen evolution and reduction reactions (OER and ORR), is subject to spin-selection rules due to the triplet ground state of O 2 . Traditional catalysts, often in singlet spin states, suffer from inefficient spin-incoherent electron transfer, which hampers reaction kinetics. Recent advances demonstrate that ferromagnetic materials, through spin-polarized charge transport and coherent spin alignment, can facilitate these challenging transformations more efficiently than antiferromagnetic analogues. This frontier article examines how magnetic ordering, superexchange interactions, and spin state alignment influence catalytic performance, with a focus on perovskite and spinel-type oxides and their emerging chalcogenide analogues. The inclusion of mixed-anion chemistry further enhances the tunability of electronic and magnetic structures. Looking ahead, ab initio simulations such as spin-polarized density functional theory (DFT) will be critical for unveiling spin-related mechanisms and guiding the rational design of next-generation spin-active catalysts. By integrating spin dynamics into catalyst design, spintro-catalysis offers a transformative approach for energy conversion and sustainable chemical transformations. The emerging field of spintro-catalysis, at the interface of catalysis and spintronics, offers a compelling strategy to overcome long-standing limitations in catalytic reactions involving spin-sensitive intermediates.